2020
DOI: 10.1515/iral-2019-0116
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pragmatic instruction on EFL teenagers’ apologetic email writing: Comprehension, production, and cognitive processes

Abstract: This study examined the effects of explicit instruction on EFL learners’ apologetic email writing in terms of comprehension, production, and cognitive processes in pragmatic performance. Participants were 30 Taiwanese EFL eighth graders who received a 10-week pragmatic training on email apologies. Research instruments were a multiple-choice test (MCT), a written discourse completion task (WDCT), and retrospective verbal reports (RVRs). The results showed that the participants obtained higher scores in the MCTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 54 publications
6
7
0
Order By: Relevance
“…This demonstrates that students perceptions of the effectiveness of utilizing Google Classroom as part of their educational experience are relatively positive, as they do care and pay attention on assignments given by students on Google Classroom and willing to complete it on time. This evidence is similar to the one stated by experts (Gardner, 2001;Lin & Wang, 2020;Santos, 2021). In particular, the greatest scores associated with handing out tasks through Google Classroom were 72 percent, which corresponds to as many as 17 students.…”
Section: Learning Commitmentsupporting
confidence: 90%
See 3 more Smart Citations
“…This demonstrates that students perceptions of the effectiveness of utilizing Google Classroom as part of their educational experience are relatively positive, as they do care and pay attention on assignments given by students on Google Classroom and willing to complete it on time. This evidence is similar to the one stated by experts (Gardner, 2001;Lin & Wang, 2020;Santos, 2021). In particular, the greatest scores associated with handing out tasks through Google Classroom were 72 percent, which corresponds to as many as 17 students.…”
Section: Learning Commitmentsupporting
confidence: 90%
“…The findings show that the intrinsic motivation of the students in learning English received quite positive responses in almost all indicators of it, as students mainly preferred a good statement. This shows that the utilization of Google Classroom in teaching English in that school can bring a good impact and make students become highly motivated in their learning, which is in agreement several theories that has been explained (Lin & Wang, 2020;Santos, 2021).…”
Section: Intrinsic Motivationsupporting
confidence: 87%
See 2 more Smart Citations
“…Chen et al [52] highlighted the importance of incorporating email-writing into language pedagogy, arguing that "email is not a monolithic genre but is inherently fluid" (p. 28), reflecting interpersonal communication and negotiation abilities. Previous studies on email literacy have focused primarily on requests and apologies (e.g., [46,[53][54][55][56]) and comparatively less on invitation, which is also a frequently occurring speech act in student-teacher interactions [57]. These studies showed that the emails produced by L2 learners are different from those produced by native speakers of the target language.…”
Section: Literature Reviewmentioning
confidence: 99%